Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Pemecahan Masalah Siswa - Zidan Maulana; Endang Hardi; Romdah Romansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on students' problem-solving skills in Biology subjects. The research employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest Design. The participants were 32 students of class X MIPA 1 at SMA Negeri 1 Baregbeg. The instrument used was an essay test designed to measure problem-solving skills, covering indicators such as understanding problems, planning solutions, implementing strategies, and evaluating outcomes. The results showed an increase in the average score from 52.13 (pretest) to 78.25 (posttest), with an N-Gain value of 0.63, categorized as moderate. These findings indicate that the PBL model effectively enhances students’ problem-solving abilities. The problem-based learning process encourages active engagement, critical thinking, and deeper conceptual understanding. This research recommends the consistent implementation of PBL to support contextual and collaborative classroom learning.